The Influence of Hop Latent Viroid (HLVd) Infection on Gene Expression and Secondary Metabolite Contents in Hop (Humulus lupulus L.) Glandular Trichomes - Patzak, Josef; Henychová, Alena; Krofta, Karel; Svoboda, Petr; Malířová, Ivana (Plants (Basel, Switzerland), 2021)
Viroids are small infectious pathogens, composed of a short single-stranded circular RNA. Hop (Humulus lupulus L.) plants are hosts to four viroids from the family Pospiviroidae. Hop latent viroid (HLVd) is spread worldwide in all hop-growing regions without any visible symptoms on infected hop plants. In this study, we evaluated the influence of HLVd infection on the content and the composition of secondary metabolites in maturated hop cones, together with gene expression analyses of involved biosynthesis and regulation genes for Saaz, Sládek, Premiant and Agnus cultivars. We confirmed that the contents of alpha bitter acids were significantly reduced in the range from 8.8% to 34% by viroid infection. New, we found that viroid infection significantly reduced the contents of xanthohumol in the range from 3.9% to 23.5%. In essential oils of Saaz cultivar, the contents of monoterpenes, terpene epoxides and terpene alcohols were increased, but the contents of sesquiterpenes and terpene ketones were decreased. Secondary metabolites changes were supported by gene expression analyses, except essential oils. Last-step biosynthesis enzyme genes, namely humulone synthase 1 (HS1) and 2 (HS2) for alpha bitter acids and O-methytransferase 1 (OMT1) for xanthohumol, were down-regulated by viroid infection. We found that the expression of ribosomal protein L5 (RPL5) RPL5 and the splicing of transcription factor IIIA-7ZF were affected by viroid infection and a disbalance in proteosynthesis can influence transcriptions of biosynthesis and regulatory genes involved in of secondary metabolites biosynthesis. We suppose that RPL5/TFIIIA-7ZF regulatory cascade can be involved in HLVd replication as for other viroids of the family Pospiviroidae.
Keywords: HLVd; essential oils; hop; xanthohumol; differential gene expression; bitter acids content; Humulus lupulus; hop latent viroid